L’importation du maas (mobility as a service) en France : un nouvel instrument pour les politiques de transport ? - Pierre-André Horth; Philippe Menerault; Cyprien Richer (Netcom)
This article studies MaaS (Mobility as a Service) in France as an instrument of transport policies. Between the importation of the concept born in Finland and a heritage of pre-existing devices in France, this article attempts to understand the nature and challenges of a "French way" for the development of MaaS. Although it benefits from the support of public policies, MaaS is still struggling to find its way among the scales of transport organizing authorities. This work questions the reproduction of the silos of public policy while MaaS carries the promise of multimodal mobility, more fluid and intuitive despite the diversity of operators.